Trends and Drivers of Agricultural Investments and Growth in Nigeria: The Pre and Financial Sector Reforms Experience - J, Akpaeti Aniekan; E, Bassey Nsikan; S, Okoro Udeme; K, Nkeme Kesit (Asian Journal of Economic Modelling, 2014)
This study examined the growth rates in agricultural investments and output in Nigeria from 1970-2009 using ordinary least square in a time series analysis. Findings revealed that agricultural investments and growth recorded a growth rate of 37.44 percent and 30.47 percent in the pre-financial sector reform periods. The result for the financial sector reform periods showed a growth rate of 23.00 percent and 7.04 percent for agricultural investment and growth respectively. The differences in growth rates were not significantly different at 5 percent (tcal < ttab at P=0.5) between the periods. There was also deceleration in growth of agricultural investments in the two periods under consideration, implying that financial sector reform might have brought an overall decrease in agricultural investments in the two periods. Also, while there was stagnation in the growth process of agricultural output in the pre-financial sector reform periods, there was acceleration in the financial sector reform periods. Hence, policies and sound regulatory framework that would enhance the development of a strong, healthy and dynamic financial system should be pursued. Such policies should be tailored towards the provision of sound infrastructures and macroeconomic stability that would create incentives for agricultural investment and growth of business opportunities on a sustainable basis and foster the expansion of financial institutions.